1993
DOI: 10.3109/08916939309077367
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity to Interleukins of CDS and CDS Anti-Dna Antibody-Producing B Cells in Murine Lupus

Abstract: We studied the effects of interleukins (IL) on in vitro IgM and IgG anti-DNA antibody production by splenic B cells from autoimmune disease-prone NZBxNZW (NZB/W) F1 mice. It was found that different interleukins regulate phenotypically distinct B cells producing separate isotype of anti-DNA antibodies. IL-2 slightly but significantly inhibited the production of IgM anti-DNA antibodies. IL-4 and IL-6 significantly enhanced the antibody production, but the effects were not so marked and inconsistent, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…67,68 In aged lupus MRL/lrp mice, increased serum levels of IL-6 were determined, 69 and in aged lupus NZBxNZB mice, IL-6 was reported to enhance the IgG anti-DNA antibody production by splenic B cells. 70 Analysis of the frequencies of leukocyte subpopulations in peripheral blood revealed an increased frequency of CD8 þ T cells positive for the differentiation marker, Ly-6C. The CD8 þ T-cell specificity might partly be explained by the fact that Ly-6C is not found on CD4 þ T cells in Ly-6.1 background strains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…67,68 In aged lupus MRL/lrp mice, increased serum levels of IL-6 were determined, 69 and in aged lupus NZBxNZB mice, IL-6 was reported to enhance the IgG anti-DNA antibody production by splenic B cells. 70 Analysis of the frequencies of leukocyte subpopulations in peripheral blood revealed an increased frequency of CD8 þ T cells positive for the differentiation marker, Ly-6C. The CD8 þ T-cell specificity might partly be explained by the fact that Ly-6C is not found on CD4 þ T cells in Ly-6.1 background strains.…”
Section: Discussionmentioning
confidence: 95%
“…54,85 In addition, increased IL-6 levels have been reported to induce development of the SLE-like phenotype in murine models. 34,69,70 The clinical outcome of SLE often is diverse, as it was described for human triplets with SLE carrying the identical mutation, 86 and not every of the existing mouse models is showing all LE criteria. 87 Thus, the development of all SLE criteria may be due to multigenetic effects.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the former, the selfgenerating B-1 population has been traditionally recognized by its expression of CD5 and its comparatively low expression of IgD (34,35). However, only rodents and primates express IgD (8) and CD5 expression can change with age and antigenic stimulation (36,37). Moreover, the studies in different species showed discrepancy between expression CD5 and fetal vs conventional B cell lineage commitment (34,35,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the immediate precusor of CD5-sIgM-sIgG+ B cells involved in IgG anti-DNA antibody production, we sorted sIgM+ B cells with and without CD5 expression from NZB/W F1 mice aged 6 months (the time when IgG anti-DNA repertoire begins to generate) and compared their in vitro potential to produce IgG anti-DNA antibodies. The results showed that IgG anti-DNA antibodies were mainly produced by CD5+sIgM+ B cells, particularly in the presence of IL-6 (Kanno et al 1993). As the total IgG synthesis was also promoted by IL-6 to a much greater extent in CD5+sIgM+ than in CD5-sIgM+ B cells, the former population of B cells from NZB/W F1 mice at this age probably contains cells going through the process of maturation, including IgM to IgG isotype switching (IgM/IgG double producers).…”
Section: Cd5 B Cells In Autoimmune Disease and B-cllmentioning
confidence: 98%